Negative pole piece, lithium ion battery and electronic equipment

By setting a double-layer active material layer on the negative electrode sheet of the lithium-ion battery and adjusting the coverage area of ​​the adhesive, the problem of difficulty in improving the energy density and fast charging capacity at the same time in the prior art is solved, and more efficient battery performance is achieved.

CN119905517APending Publication Date: 2025-04-29ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510144976.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the energy density and fast charging capability of lithium-ion batteries. High compaction density will reduce lithium ions diffusion, while the super-thick active layer will hinder fast charging performance.

Method used

The negative electrode sheet with a double-layer structure is adopted. The first coating and the second coating respectively contain different proportions of adhesives to cover active substances. By adjusting the coverage area of ​​the adhesive M1 and M2, the impedance and bonding ability of the negative electrode sheet are regulated.

Benefits of technology

It achieves the purpose of taking into account energy density and fast charging capabilities, and improves the overall performance of lithium-ion batteries, including charging performance, safety performance and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905517A_ABST
    Figure CN119905517A_ABST
Patent Text Reader

Abstract

The negative pole piece comprises a current collector and an active material layer located on the current collector. The active material layer comprises a first coating layer and a second coating layer which are laminated. The second coating is located between the current collector and the first coating. The first coating layer includes a first active material, a first conductive agent, a first adhesive, and a first dispersant. The second coating layer contains a second active material, a second conductive agent, a second adhesive, and a second dispersant. The ratio of the area, coated by the first adhesive, of the first active substance to the total surface area of the first active substance is M1, the ratio of the area, coated by the second adhesive, of the second active substance to the total surface area of the second active substance is M2, M1 is smaller than M2, M1 is 0.1%-3%, and M2 is 3%-100%. The active material layer with a double-layer structure is arranged on the current collector, so that the purpose of considering both energy density and quick charge capacity is achieved. The invention also provides a lithium ion battery and electronic equipment comprising the negative pole piece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode plate, a lithium-ion battery comprising the negative electrode plate, and an electronic device comprising the lithium-ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high voltage, stable discharge voltage, clean and environmentally friendly, and have been widely used in portable electronic devices, electric vehicles and energy storage grids. With the vigorous development of the lithium battery industry and the growing technological demand, improving energy density and fast charging capabilities has always been an urgent problem to be solved.

[0003] In terms of the battery's pole piece structure, for traditional pole pieces that only have a single active layer on the current collector, if you want to increase the energy density, it is generally achieved by increasing the compaction density of the single active layer or increasing the thickness of the active layer. However, high compaction will reduce the pole piece porosity and hinder the diffusion of lithium ions. In addition to the longer lithium ion diffusion path, the pole piece with an ultra-thick active layer also places higher requirements on the electrode conductive network, which will deteriorate the fast charging performance. In terms of material technology, the energy density can be improved by regulating the particle size of the main material of the active layer. For example, the large and small particle sizes are matched in a certain proportion to improve compaction and thus improve the energy density. However, if you want to improve the fast charging capability, you often need to design the main material of the active layer into small particles to increase the interface reaction sites. Obviously, this is contrary to the idea of ​​improving energy density. It can be seen that it is difficult for existing technologies to simultaneously take into account the improvement of energy density and fast charging capability. Summary of the invention

[0004] In view of this, the first aspect of the present application provides a negative electrode sheet, comprising a current collector and an active material layer located on at least one surface of the current collector, wherein the active material layer comprises a first coating layer and a second coating layer stacked, wherein the second coating layer is located between the current collector and the first coating layer; The first coating layer comprises a first active material, a first conductive agent, a first adhesive and a first dispersant; the second coating layer comprises a second active material, a second conductive agent, a second adhesive and a second dispersant; a ratio of an area of ​​the first active material coated by the first adhesive to a total surface area of ​​the first active material is M1; a ratio of an area of ​​the second active material coated by the second adhesive to a total surface area of ​​the second active material is M2; M1 is less than M2; M1 is 0.1% to 3%; and M2 is 3% to 100%.

[0005] The present application achieves the goal of taking both energy density and fast charging capability into consideration by setting a double-layer active material layer on the negative electrode current collector and regulating the area ratio M1 of the first active material coated by the first adhesive of the first coating and the area ratio M2 of the second active material coated by the second adhesive of the second coating, thereby regulating the impedance and bonding ability of the negative electrode plate.

[0006] In some embodiments, the glass transition temperature Tg of the first adhesive is greater than 5°C, and the glass transition temperature Tg of the second adhesive is less than -10°C.

[0007] In some embodiments, the added mass percentage of the first adhesive in the first coating is A, and the added mass percentage of the second adhesive in the second coating is B, wherein the ratio of B:A ranges from 0.2 to 0.8.

[0008] In some embodiments, the compacted density of the second coating is greater than or equal to the compacted density of the first coating.

[0009] In some embodiments, the thickness of the first coating layer is 10-100 μm, and the thickness of the second coating layer is 10-100 μm.

[0010] In some embodiments, the first active material and the second active material are both selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, lithium titanate, silicon-based materials, and composite materials of graphite and silicon.

[0011] In some embodiments, the second active material comprises a silicon-based material.

[0012] In some embodiments, in the first coating layer, the weight ratio of the first active material, the first conductive agent, the first adhesive and the first dispersant may be (80-99.5): (0.1-15): (0.1-15): (0.1-10); In the second coating layer, the weight ratio of the second active material, the second conductive agent, the second adhesive and the second dispersant can be (80~99.5):(0.1~15):(0.1~15):(0.1~10).

[0013] A second aspect of the present application provides a lithium-ion battery, comprising the above-mentioned negative electrode plate and positive electrode plate.

[0014] A third aspect of the present application provides an electronic device, comprising the above-mentioned lithium-ion battery.

[0015] The lithium-ion battery mentioned above is used as a power source for electronic devices. The lithium-ion battery has stable performance and can stably provide power for the electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a cross-sectional schematic diagram of the negative electrode sheet of the embodiment of the present application.

[0017] Figure 2 This is a scanning electron microscope image of a binder coated on the negative electrode active material (graphite).

[0018] Figure 3 This is a scanning electron microscope image of another type of adhesive coated on the negative electrode active material (graphite).

[0019] Figure 4 This is a scanning electron microscope image of another adhesive coated on the negative electrode active material (graphite).

[0020] Description of main component symbols: Negative electrode sheet 100 , current collector 10 , active material layer 30 , first coating layer 31 , and second coating layer 32 . DETAILED DESCRIPTION

[0021] In order to more clearly understand the purpose, features and advantages of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that, in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other. In the following description, many specific details are set forth to facilitate a full understanding of the present application, and the embodiments described are only a part of the embodiments of the present application, rather than all of the embodiments.

[0022] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, it should be noted that the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0024] The following will describe some embodiments of the present application in detail with reference to the accompanying drawings. The data range values ​​recorded in the present application shall include the end values ​​unless otherwise specified.

[0025] The present application provides a negative electrode plate, which can be used in lithium-ion batteries. Figure 1As shown, the negative electrode sheet 100 of the embodiment of the present application includes a current collector 10 and an active material layer 30 located on at least one surface of the current collector 10. In this embodiment, the active material layer 30 is located on two opposite surfaces of the current collector 10. The active material layer 30 includes a first coating layer 31 and a second coating layer 32 that are stacked, wherein the second coating layer 32 is located on the surface of the current collector 10, and the first coating layer 31 is located on the surface of the second coating layer 32 away from the current collector 10. The second coating layer 32 is located between the current collector 10 and the first coating layer 31.

[0026] The first coating 31 includes a first active material, a first conductive agent, a first adhesive, and a first dispersant. The second coating 32 includes a second active material, a second conductive agent, a second adhesive, and a second dispersant. In the negative electrode coating, the negative electrode active material accounts for a large proportion, and the adhesive is basically coated on the surface of the active material.

[0027] The first adhesive coats the surface of the first active material, and the second adhesive coats the surface of the second active material. The ratio of the area of ​​the first adhesive coating the first active material to the total surface area of ​​the first active material is M1. The ratio of the area of ​​the second adhesive coating the second active material to the total surface area of ​​the second active material is M2. Among them, M1 is less than M2. In some embodiments, M1 is 0.1% to 3%, for example, M1 may be 0.1%, 0.3%, 0.5%, 0.7%, 1%, 1.3%, 1.5%, 1.7%, 2%, 2.3%, 2.5%, 2.7%, 3%. M2 is 3% to 100%, for example, M2 may be 3%, 7%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 100%.

[0028] In the present application, the area ratio M of the active material coated by the adhesive can be obtained through Raman testing.

[0029] The following is an example of using styrene-butadiene rubber (SBR) as an adhesive. The principle of Raman testing to characterize the coating of SBR is as follows: the negative electrode is generally composed of graphite, CMC / SBR, and the characteristic peaks of graphite are 1360 / 1580 / 2700cm -1 , SBR characteristic peak position 1001 / 2930 cm -1 , corresponding to the benzene ring structure and CH bond, respectively. The characteristic peak of CMC is 2930 cm -1 , corresponding to the CH bond on its main chain. In Raman testing, when the 1001 / 2930 cm -1 The presence of SBR on the surface can be determined by the characteristic peaks at the position. The coating of SBR on the surface can be confirmed by performing Raman scanning on different areas of the pole piece.

[0030] The specific test method is: a micro-area Raman spectrometer (HORIBA LabRAM HR) is used to perform spectral analysis on the negative electrode. A 514 nm laser is used as the excitation source. The power of the laser after passing through the quartz window is about 0.8 mW, the integration time is 10 s, and the integration is twice to improve the signal-to-noise ratio. Through a 50x telephoto lens, the spot diameter of the laser is about 1 μm. A 31μm × 34μm grid area was scanned with a grid spacing of 2.5 μm. A total of 156 spectra were obtained each time to form a Raman image. The area ratio of the imaging area of ​​SBR to the total area is calculated as the area ratio of the SBR-coated active substance.

[0031] The binder is a high molecular polymer material, which is distributed in the coating of the negative electrode to play the role of bonding the components, thereby providing a certain bonding strength to the coating. The binder is usually an electronic and ion inert material. When coated on the surface of the active material, it will increase the resistance and ion diffusion path, thereby increasing the battery impedance. Therefore, the larger the M value of the binder-coated active material, the greater the battery impedance and the worse the fast charging capability. On the contrary, the smaller the M value of the binder-coated active material, the smaller the battery impedance and the better the fast charging capability.

[0032] When the battery is charged, the lithium insertion pressure of the first coating 31 located on the surface is large, and the lithium insertion pressure of the second coating 32 located in the middle is relatively small. The negative electrode plate of the present application is provided with a double-layer active layer (first coating 31 and second coating 32), and the first adhesive in the first coating 31 is provided to cover less area of ​​the first active material, thereby reducing the impedance of the first coating 31. In this way, the negative electrode plate 100 ensures fast charging capability through the first coating 31; at the same time, the second adhesive in the second coating 32 covers more area of ​​the second active material, thereby ensuring the bonding strength of the second coating 32.

[0033] In some embodiments, the glass transition temperature Tg of the first adhesive is greater than 5° C., for example, about 7° C., 10° C., 15° C., 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., 80° C., 100° C., 150° C., 170° C., 200° C. The adhesive with a glass transition temperature Tg greater than 5° C. can better maintain the initial particle morphology at the ambient temperature of the battery, has less coating on the negative electrode surface, can reduce electronic resistance and improve lithium ion transmission distance, thereby improving the kinetics of the first coating 31 of the negative electrode.

[0034] In some embodiments, the glass transition temperature Tg of the second adhesive is less than -10°C, for example, about -15°C, -20°C, -25°C, -30°C, -35°C, -40°C, -45°C, -50°C, -55°C, -60°C, -65°C, -70°C, -80°C, -90°C, -100°C, -110°C, -115°C. The adhesive with a glass transition temperature Tg less than -10°C has a more active molecular chain at the ambient temperature of the battery, has a stronger bonding ability, can achieve good coating on the negative electrode surface, and greatly improves the bonding ability of the negative electrode second coating 32.

[0035] The glass transition temperature of the adhesive can be controlled by adjusting the ratio of soft and hard segment monomers, enhancing intermolecular hydrogen bonding, and regulating the degree of crosslinking.

[0036] The first adhesive and the second adhesive can be selected from one or more of polyacrylamide, polyvinyl alcohol, styrene-butadiene emulsion, styrene-acrylic emulsion and pure acrylic emulsion.

[0037] The first adhesive further contains functional monomers, which include one or more of sulfonic acid groups, nitrile groups, and ester groups, which can enhance the affinity between the adhesive and the electrolyte or improve the ion conductivity, and further improve the dynamics of the first coating 31 .

[0038] In the present application, the second coating 32 uses a second adhesive with a glass transition temperature Tg < -10°C, and its bonding ability is greatly enhanced. Therefore, the amount of the second adhesive in the second coating 32 can be reduced, thereby increasing the amount of the second active material, thereby improving the overall energy density of the negative electrode.

[0039] In some embodiments, the added mass percentage of the first adhesive in the first coating 31 is A, and the added mass percentage of the second adhesive in the second coating 32 is B, wherein the ratio of B / A ranges from 0.2 to 0.8, for example, the ratio of B / A may be 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, and 0.8.

[0040] Figures 2 to 4 The scanning electron microscope images of three different adhesives coated on the negative electrode active material (graphite) are shown. The large gray particles in the image are graphite, and the dark black represents the adhesive. Figure 2 The adhesive used is styrene-butadiene rubber SBR-A, and the glass transition temperature Tg is about -3°C. Figure 3 The adhesive used is styrene-butadiene rubber SBR-B, and the glass transition temperature Tg is about 18°C. Figure 4 The adhesive used is styrene-butadiene rubber SBR-C, and the glass transition temperature Tg is about -25°C.

[0041] in accordance with Figures 2 to 4 It can be seen that Figure 3 Among them, the glass transition temperature Tg of the adhesive SBR-B is the largest, the adhesive maintains a complete granular morphology, and the area of ​​the coated graphite accounts for the smallest proportion. Figure 4 The glass transition temperature Tg of the binder SBR-C is the smallest, and the binder is observed to deform significantly, achieving good coverage of graphite. Figure 2 In the figure, the glass transition temperature Tg of the binder SBR-A is in the middle, and its area ratio of coated graphite is also in the middle. This fully demonstrates that the area ratio M value of the active material coated by the binder can be effectively regulated by the glass transition temperature Tg of the binder.

[0042] In some embodiments, the thickness of the first coating 31 is 10-100 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, and the thickness of the second coating 32 is 10-100 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm.

[0043] Furthermore, in the present application, the compaction density of the second coating 32 is greater than or equal to the compaction density of the first coating 31 to further improve the energy density.

[0044] The second coating 32 located in the middle of the pole piece can reduce the amount of the second adhesive to a certain extent, add more second active material, and improve the energy density. The lithium insertion pressure of the second coating 32 is relatively small, and a larger compaction density can be used. The energy density can be further improved by combining these two methods.

[0045] The first active material and the second active material are both selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, lithium titanate, silicon-based materials, and composite materials of graphite and silicon. The first coating 31 and the second coating 32 can freely select negative electrode active materials and be flexibly designed. They can be materials of the same type and physical properties (for example, the first active material and the second active material are both artificial graphite), materials of the same type with different physical properties (for example, the first and second active materials are both artificial graphite, but with different particle size distributions), and materials of different types and physical properties (for example, the first active material is natural graphite and the second active material is silicon-carbon material) to meet the needs of various chemical systems.

[0046] In some embodiments, the second active material of the second coating 32 contains silicon-based materials. The high coating property of the second adhesive can suppress the high expansion of the silicon-based materials, reduce material breakage and damage to the bonding network and the conductive network, and improve battery life.

[0047] In the embodiment of the present application, in the first coating 31, the weight ratio of the first active material, the first conductive agent, the first adhesive and the first dispersant can be (80~99.5): (0.1~15): (0.1~15): (0.1~10).

[0048] In the embodiment of the present application, in the second coating 32, the weight ratio of the second active material, the second conductive agent, the second adhesive and the second dispersant can be (80~99.5):(0.1~15):(0.1~15):(0.1~10).

[0049] The first conductive agent and the second conductive agent may be selected from one or more of furnace black, acetylene black, Ketjen black, carbon nanotubes, carbon nanofibers, and graphene.

[0050] The first dispersant and the second dispersant may be selected from one or more of sodium carboxymethyl cellulose (CMC-Na) and lithium carboxymethyl cellulose (CMC-Li).

[0051] In some embodiments, the negative electrode current collector includes, but is not limited to: copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof. In some embodiments, the negative electrode current collector is copper foil.

[0052] The present application adjusts the impedance and bonding capacity of the negative electrode sheet by setting a double-layer active material layer on the negative electrode current collector and adjusting the area ratio M1 of the first adhesive of the first coating layer covering the first active material and the area ratio M2 of the second adhesive of the second coating layer covering the second active material. In addition, the composition of the first coating layer and the second coating layer is optimized to achieve the purpose of taking into account both energy density and fast charging capacity.

[0053] The negative electrode plate of the present application has excellent charging performance due to its good lithium embedding ability; it can prevent lithium precipitation and improve safety performance; the overall compaction density of the active material layer is high, the active material loading is increased, and the energy density is high; the bonding performance is good, which can inhibit the expansion of graphite or silicon negative electrodes and improve the cycle life.

[0054] The present application also provides a lithium-ion battery, comprising the above-mentioned negative electrode sheet, a positive electrode sheet and an electrolyte. In some embodiments, the lithium-ion battery may further include a separator disposed between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.

[0055] positive electrode The positive electrode active material layer mainly includes positive electrode active materials. The specific types of positive electrode active materials are not subject to specific restrictions and can be selected according to needs.

[0056] In some embodiments, the positive electrode active material includes a compound that reversibly intercalates and deintercalates lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel. In some embodiments, the positive electrode active material is selected from at least one of the following: lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), lithium iron phosphate (LiFePO4), lithium nickel cobalt manganese oxide or lithium-rich manganese materials.

[0057] In some embodiments, the positive electrode active material layer further includes a binder and optionally a conductive material. The binder can improve the bonding between the positive electrode active material particles and can improve the bonding between the positive electrode active material and the positive electrode current collector. In some embodiments, the binder includes, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin and nylon, etc.

[0058] In some embodiments, the positive electrode active material layer also includes a conductive material to impart conductivity to the electrode. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0059] In some embodiments, the positive electrode current collector is a metal, such as but not limited to aluminum foil.

[0060] In some embodiments, the structure of the positive electrode is a positive electrode structure known in the art and can be used in lithium-ion batteries.

[0061] In some embodiments, the preparation method of the positive electrode is a preparation method of the positive electrode that can be used for lithium-ion batteries that is well known in the art. For example, the positive electrode can be obtained by the following method: mixing the active material, the conductive material, the binder and the above-mentioned positive electrode additive in a solvent to prepare a positive electrode active material slurry, and coating the positive electrode active material slurry on the current collector, drying, and cold pressing to form a positive electrode active material layer. In some embodiments, the solvent may include water, N-methylpyrrolidone, etc., but is not limited thereto.

[0062] Electrolyte The electrolyte used in the embodiments of the present application may be an electrolyte known in the prior art. The electrolyte may be divided into an aqueous electrolyte and a non-aqueous electrolyte. Compared with an aqueous electrolyte, a lithium-ion battery using a non-aqueous electrolyte can operate in a wider voltage window, thereby achieving a higher energy density. In some embodiments, the non-aqueous electrolyte includes an organic solvent, an electrolyte, and an additive.

[0063] The electrolytes that can be used in the electrolyte of the embodiments of the present application include, but are not limited to: inorganic lithium salts, such as LiClO4, LiAsF6, LiPF6, LiBF4, LiSbF6, LiSO3F, LiN(FSO2)2, etc.; fluorine-containing organic lithium salts, such as LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonyl imide lithium, cyclic 1,2-tetrafluoroethane disulfonyl imide lithium, LiPF4(CF3)2, LiN(C F3SO2)(C4F9SO2), LiC(CF3SO2)3, LiPF4(CF3SO2)2, LiPF4(C2F5)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium salts containing dicarboxylic acid complexes, such as lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, lithium tetrafluoro(oxalato)phosphate, etc. In addition, the above-mentioned electrolytes can be used alone or in combination of two or more. For example, in some embodiments, the electrolyte includes a combination of LiPF6 and LiBF4. In some embodiments, the electrolyte includes LiPF6. In some embodiments, based on the mass of the electrolyte, the mass percentage of the electrolyte is in the range of 8% to 15%.

[0064] The additives that can be used in the electrolyte of the present application can be additives that are known in the art and can be used to improve the electrochemical performance of the battery. In some embodiments, the additives include, but are not limited to, at least one of polynitrile compounds, sulfur-containing additives, fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), and 1,4-butane sultone.

[0065] The organic solvent that can be used in the electrolyte of the present application can be any organic solvent known in the prior art. In some embodiments, the organic solvent includes, but is not limited to: carbonate compounds, ester-based compounds, ether-based compounds, ketone-based compounds, alcohol-based compounds, aprotic solvents, or combinations thereof. Among them, examples of carbonate compounds include, but are not limited to, linear carbonate compounds, cyclic carbonate compounds, fluorinated carbonate compounds, or combinations thereof.

[0066] In some embodiments, the organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, methyl acetate or ethyl propionate.

[0067] The preparation method of the electrolyte of the embodiment of the present application is not limited, and can be prepared in the manner of a conventional electrolyte. In some embodiments, the electrolyte of the present application can be prepared by mixing the components.

[0068] Isolation film In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0069] For example, in some embodiments, the isolation film includes a substrate layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure. The material of the substrate layer can be selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, the material of the substrate layer can be selected from polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film.

[0070] A surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer can be a polymer layer, an inorganic layer or a layer formed by a mixed polymer and an inorganic substance. Specifically, the inorganic layer includes inorganic particles and a bonding agent. The inorganic particles can be selected from one or more combinations of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The bonding agent can be selected from one or more combinations of polyvinylidene fluoride, a polymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0071] The present application provides an electronic device, which includes the above-mentioned lithium-ion battery.

[0072] The use of the lithium-ion battery of the present application is not particularly limited, and it can be used in any electronic device known in the prior art. For example, the electronic device includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0073] The technical solution of the embodiment of the present application is further illustrated by means of specific examples below.

[0074] Comparative Example 1 Graphite, acetylene black, styrene-butadiene rubber (code-named SBR-A) and sodium carboxymethyl cellulose are added into a stirring tank in a mass ratio of 95.8:1:2:1.2, and then deionized water is added. After stirring evenly, the negative electrode slurry is prepared and evenly coated on the surface of the copper foil by a coater, followed by drying and compacting with a roller press to obtain a negative electrode sheet.

[0075] The positive electrode active material lithium iron phosphate, acetylene black, multi-walled carbon nanotubes, and adhesive polyvinylidene fluoride are added to a stirring tank in a mass ratio of 97.2:0.7:0.3:1.8, and then NMP solvent is added. After stirring evenly, the positive electrode slurry is prepared. The positive electrode slurry is evenly coated on the surface of the aluminum foil by a coating machine, and then dried and compacted by a roller press to obtain a positive electrode sheet.

[0076] The positive electrode sheet, negative electrode sheet and separator stack sheet are sequentially formed into a battery cell, which is then packaged with aluminum-plastic film, injected with electrolyte after baking to remove moisture, and then formed by hot pressing process, and finally obtained after secondary sealing, degassing, sorting and shaping.

[0077] Example 1 The preparation methods of this embodiment and comparative example 1 are basically the same, except that the coating of the negative electrode adopts a double-layer structure, and the second coating is located between the first coating and the current collector.

[0078] The mass ratio of the second coating is graphite, acetylene black, single-walled carbon nanotubes, styrene-butadiene rubber (code-named SBR-B) and sodium carboxymethyl cellulose (CMC) in the ratio of 96.7:0.5:0.1:1.5:1.2.

[0079] The mass ratio of the first coating layer is graphite, acetylene black, styrene-butadiene rubber (code-named SBR-C) and sodium carboxymethyl cellulose in the ratio of 95.8:1:2:1.2.

[0080] Example 2 The preparation method of this embodiment is basically the same as that of embodiment 1, except that: The mass ratio of the second coating layer is graphite, acetylene black, single-walled carbon nanotubes, styrene-butadiene rubber (code-named SBR-B) and sodium carboxymethyl cellulose (CMC) according to 97.2:0.5:0.1:1:1.2.

[0081] Example 3 The preparation method of this embodiment is basically the same as that of embodiment 1, except that: The second coating uses partial silicon material, and its mass ratio is 86.7:10:0.5:0.1:1.5:1.2 for graphite, silicon dioxide, acetylene black, single-walled carbon nanotubes, styrene-butadiene rubber (code-named SBR-B) and sodium carboxymethyl cellulose (CMC); the overall silicon doping amount is 5%.

[0082] Please refer to Table 1 for the specific composition parameters of the negative electrode plate, where the upper layer represents the first coating layer and the lower layer represents the second coating layer.

[0083] Table 1 The batteries prepared in Comparative Example 1 and Examples 1-3 were subjected to energy density, direct current internal resistance (DCR), 45°C cycle and 4C lithium deposition tests. The test results are shown in Table 2.

[0084] Table 2 Compared with Comparative Example 1, the energy density of Examples 1-3 is relatively improved, the DCR is relatively reduced, the 500T capacity retention rate is relatively improved, and there is no lithium precipitation at the 4C charging interface. It can be seen that the negative electrode plate structure with a double-layer coating of the present application is adopted, and the second coating adopts a high-coating adhesive, with a lower amount of adhesive and at the same time meeting the bonding performance, contributing to the addition amount of active material, and achieving an increase in energy density. Among them, in Examples 1-2, the percentage of the second adhesive added in the second coating is 1.5% and 1% respectively, and its energy density is further improved.

[0085] In terms of electrical performance, Examples 1-2 have also been greatly improved compared to Comparative Example 1. The upper coating (first coating) adopts an extremely low coating ratio of 0.65%, which improves the conduction of electrons and ions, significantly reduces DCR, and significantly improves lithium deposition at the negative electrode interface during high-rate charging, thereby greatly improving the cycle life.

[0086] Under conventional design, due to the large volume expansion of silicon materials, their bonding and conductive networks are destroyed, and with the breakage of silicon materials, new interfaces will be continuously exposed to produce side reactions with the electrolyte, resulting in increased impedance and affecting battery life. In Example 3, a 5% silicon doping amount is used, and its energy density is greatly improved. At the same time, compared with the pure graphite system of Examples 1-2, its performance is not significantly lost, indicating that the strategy of the present invention is also applicable to silicon-containing systems. This is mainly because the lower layer of high-coating adhesives suppresses the destruction of materials to a certain extent and ensures the long-term integrity of the bonding and conductive network on the surface of the active material.

[0087] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A negative electrode sheet, comprising a current collector and an active material layer located on at least one surface of the current collector, characterized in that: The active material layer comprises a first coating layer and a second coating layer which are stacked, wherein the second coating layer is located between the current collector and the first coating layer; The first coating layer comprises a first active material, a first conductive agent, a first adhesive and a first dispersant; the second coating layer comprises a second active material, a second conductive agent, a second adhesive and a second dispersant; a ratio of an area of ​​the first active material coated by the first adhesive to a total surface area of ​​the first active material is M1; a ratio of an area of ​​the second active material coated by the second adhesive to a total surface area of ​​the second active material is M2; M1 is less than M2; M1 is 0.1% to 3%; and M2 is 3% to 100%.

2. The negative electrode sheet according to claim 1, characterized in that: The glass transition temperature Tg of the first adhesive is greater than 5°C, and the glass transition temperature Tg of the second adhesive is less than -10°C.

3. The negative electrode sheet according to claim 2, characterized in that: The added mass percentage of the first adhesive in the first coating is A, and the added mass percentage of the second adhesive in the second coating is B, wherein the ratio of B:A ranges from 0.2 to 0.

8.

4. The negative electrode sheet according to claim 1, characterized in that: The compacted density of the second coating layer is greater than or equal to the compacted density of the first coating layer.

5. The negative electrode sheet according to claim 1, characterized in that: The thickness of the first coating layer is 10-100 μm, and the thickness of the second coating layer is 10-100 μm.

6. The negative electrode sheet according to claim 1, characterized in that: The first active material and the second active material are both selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, lithium titanate, silicon-based materials and composite materials of graphite and silicon.

7. The negative electrode sheet according to claim 6, characterized in that: The second active material contains a silicon-based material.

8. The negative electrode sheet according to claim 1, characterized in that: In the first coating layer, the weight ratio of the first active material, the first conductive agent, the first adhesive and the first dispersant may be (80-99.5): (0.1-15): (0.1-15): (0.1-10); In the second coating layer, the weight ratio of the second active material, the second conductive agent, the second adhesive and the second dispersant can be (80~99.5):(0.1~15):(0.1~15):(0.1~10).

9. A lithium-ion battery, comprising a positive electrode sheet and a negative electrode sheet, characterized in that: The negative electrode plate is the negative electrode plate according to any one of claims 1 to 8.

10. An electronic device, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Negative electrode for rechargeable lithium battery, method of preparing the same and rechargeable lithium battery including the same

    CN103887507A

  • Lithium ion battery

    CN111354949A

  • Negative pole piece and electrochemical device comprising same

    CN114094041A

  • Negative plate, preparation method thereof and battery

    CN116190562A

  • Negative pole piece and lithium ion battery

    CN118053978A